Hubungan Kadar Kolesterol dan Tekanan Darah pada Lansia Yang Berkunjung ke Posyandu Lansia - Noor Rochmah Ida Ayu Trisno Putri; Etika Dewi Cahyaningrum (Universitas Harapan Bangsa, 2023)
The increase in the elderly population has an impact on the emergence of degenerative diseases such as increasing cholesterol levels which can cause heart disease, the emergence of hypertension, diabetes mellitus and other degenerative diseases. Another negative impact that arises is the existence of elderly people who have total dependence and elderly people who cannot become productive again. This study aims to determine the relationship between cholesterol levels and blood pressure in elderly people who visit posyandu. The research results show that the characteristics of the elderly are dominated by the early elderly (82.9%). female (77.1%). 34.3% of seniors had grade 1 hypertension and 57.1% had high cholesterol levels. %). The chi-square test shows that there is a relationship between cholesterol levels and blood pressure values ​​in the elderly where the p value is 0.038 (p-value <0.05). The results of this research can be used to provide educational programs to the elderly and their families regarding prevention and health care for the elderly so that they can prevent complications from other diseases.